Reprodução e recrutamento de peixes migradores do médio Rio Uruguai - Pachla, Lucas Adriano (2020)
Ecological studies aiming to understand the life cycle of migratory fish in still conserved environments are of fundamental importance for protection and preservation of natural stocks, since these species have a great socio-economic value and provide important ecological functions for the ecosystems in which they develop. In this sense, this study investigated the reproduction and recruitment of migratory fish species along an extensive river gradient in the Middle Uruguay River sub-basin, RS, Brazil. Sampling was carried out with varied fishing equipment, covering the main river and the tributary of each of the four selected sections for middle area Uruguay River, covering together approximately 650 km. Using a data set of sampling made between the years of 2015 and 2019, an assessment of distribution patterns in the composition, abundance and total length of juvenile migratory fish was performed. In addition, a second study that registers for the fist time the spawning behavior of spotted surubim Pseudoplatystoma corruscans in natural environment was carried out. Among the main results of the first study, the gradual increase in the abundance of migratory juveniles from the stretches located upstream to the downstream plain stretches and an increase in the length of juveniles from downstream to upstream can be highlighted. Furthermore, there was a greater number of smaller fishes in the tributaries than in the main river. Showing in this way that the plains and tributary rivers are fundamental as nursery areas, and that in the course of growth, there is an upward migration that distributes juveniles across the whole sub-basin. On the other hand, in the second study, it was verified that P. corruscans reproduces in shoals, in a proportion of five males for each female. In the spawning group, there is a social organization, where the larger female leads the shoal, followed by the other females and with the males positioned on the sides. In this study, polygamy of males and females, as well as a great dispute between males to fertilized the eggs were observed. Both studies show that the conservation status of the Middle Uruguay River still allows migratory species to successfully complete their reproductive cycle.